Analisis Konsep Fisika pada Proses Pembuatan Batik Gambo Musi Banyuasin - AJ, Suharli; M. Furqon; Kriswantoro; Ulfah, Fadilla; Siregar, Dwi Rayana (UNIB Press, 2024)
Physics, a branch of natural science, studies various natural phenomena, including matter and energy, and the interactions between the two. Students often struggle to understand physics concepts in school because they are theoretical and not contextual. A contextual learning approach, such as ethnophysics, is one solution to make physics more interesting and relevant. Ethnophysics integrates physics concepts with local wisdom. One of the local wisdoms in Musi Banyuasin is batik gambo. Making Batik Gambo has various potentials that can be analyzed in physics concepts during production. Therefore, this study aims to explore the physics concept in making batik Gambo. The method used is qualitative research in the form of a literature study with an ethnophysical approach. The analysis of physics concepts, such as heat transfer, pressure, capillarity, and adhesion, are involved in making Batik Gambo. Studying this physics concept facilitates theoretical understanding and becomes a contextual and exciting learning tool for students while supporting and improving scientific literacy.